Kinerja Pegawai Bidang Pengelolaan Sumber Daya Air (Psda) Pada Dinas Pekerjaan Umum Di Kabupaten Enrekang - Irmayanti, Irmayanti; Alyas, Alyas; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine how the employee’s performance and what factors affect the performance of employees in the field of Water Resources Management at the Public Works Department in Enrekang Regency. This study used a qualitative descriptive research. Data collection techniques were observation and interviews with 7 informants. The results of this study could be seen that the performance of water resources employees at Enrekang Regency Public Works Department had not run smoothly and optimally because there ware still some problems in carrying out their work, namely the problem of workload that was not appropriate due to lack of human resources, problems of supervision in the development process. The suggestions were the need for qualified human resources and could be responsible for the tasks assigned, and the existence of a strict policy from the head of the field of water resources for employees who did not complete their tasks on time.